2021
DOI: 10.3390/life11040276
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactivity of Muscarinic Acetylcholine M2 and Serotonin 5-HT2B Receptors, Norepinephrine Transporter and Kir Channels in a Model of Epilepsy

Abstract: Epilepsy is characterized by an imbalance in neurotransmitter activity; an increased excitatory to an inhibitory activity. Acetylcholine (ACh), serotonin, and norepinephrine (NE) may modulate neural activity via several mechanisms, mainly through its receptors/transporter activity and alterations in the extracellular potassium (K+) concentration via K+ ion channels. Seizures may disrupt the regulation of inwardly rectifying K+ (Kir) channels and alter the receptor/transporter activity. However, there are limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…However, these findings are in line with several studies demonstrating that inactivation of NET ameliorates seizures in animal models of epilepsy [54] and with reports that TH and NET are upregulated following seizures in animal models [55,56]. Altogether, this suggests that the ADHD-like phenotype observed in this animal model may be related to an excessive, rather than impaired, noradrenergic signalling.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, these findings are in line with several studies demonstrating that inactivation of NET ameliorates seizures in animal models of epilepsy [54] and with reports that TH and NET are upregulated following seizures in animal models [55,56]. Altogether, this suggests that the ADHD-like phenotype observed in this animal model may be related to an excessive, rather than impaired, noradrenergic signalling.…”
Section: Discussionsupporting
confidence: 91%
“…Altogether, this suggests that the ADHD-like phenotype observed in this animal model may be related to an excessive, rather than impaired, noradrenergic signalling. Alternatively, the impairment in serotonergic signalling that is concomitantly observed [36,56] may be the determinant factor in this respect. This question should be further investigated but is currently beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…This is overall conflicting with previous knowledge that noradrenaline levels are decreased in the Li 2+ -pilocarpine model, and that this is related to depression-like symptoms [ 38 ]. However, these findings are in line with several studies demonstrating that inactivation of NET ameliorates seizures in animal models of epilepsy [ 56 ], and with reports that TH and NET are upregulated following seizures in animal models [ 57 , 58 ]. Altogether, this suggests that the ADHD-like phenotype observed in this animal model may be related to an excessive, rather than impaired, noradrenergic signalling.…”
Section: Discussionsupporting
confidence: 89%
“…First, in a PTZ‐kindling rat model of chronic epilepsy increased immunoreactivity of the 5‐HT 2B receptor was found in the cortex and medulla, while it was decreased in the hippocampus. However, further behavioral/functional studies are necessary to elucidate the meaning of this immunoreactivity alteration 95 . Second, the novel ASM, CBD, reduced seizures in pilocarpine‐induced SE in rats that was attributed to both CB 1 and 5‐HT 2B receptors, 96 although 5‐HT 2B receptors are probably not involved in CBD's mechanism of action as shown by Dos Santos et al 48 and Pelz et al 97 Third, Baraban et al showed that 5‐HT 2B agonists can reduce seizures in the zebrafish DS model.…”
Section: Resultsmentioning
confidence: 99%
“…However, further behavioral/functional studies are necessary to elucidate the meaning of this immunoreactivity alteration. 95 Second, the novel ASM, CBD, reduced seizures in pilocarpine-induced SE in rats that was attributed to both CB 1 and 5-HT 2B receptors, 96 although 5-HT 2B receptors are probably not involved in CBD's mechanism of action as shown by Dos Santos et al 48 and Pelz et al 97 Third, Baraban et al showed that 5-HT 2B agonists can reduce seizures in the zebrafish DS model. Nonetheless, numerous other researchers did not observe any seizure reduction by 5-HT 2B modulation in different animal models of epilepsy.…”
Section: Ht 2c Receptorsmentioning
confidence: 99%